High Strength Concrete Containing Silica Fume And Metakaolin - Liew, Kam Wah (Universiti Sains Malaysia, 2005)
The effect of silica fume (SF) and metakaolin (MK) on properties of high strength concrete mixes containing 0%, 10% and 15% silica fume and metakaolin as partial replacement of cement has been investigated. Experimental studies have been conducted to determine the influence of both mineral admixtures on the workability, strength development, surface hardness, porosity and permeability of high strength concrete. The slump, compacting factor, plastic density, compressive strength, Rebound number, ultrasonic pulse velocity, porosity and permeability tests were performed. The specimens were cured in water for periods varying from 1, 3, 7, 28 to 56 days before testing. It was observed that the specimens with 15% silica fume had the highest compressive strength, ultrasonic pulse velocity, Rebound number, lowest porosity and permeability at the age of 56 days. Whereas, the specimens with metakaolin had the compressive strength, ultrasonic pulse velocity, Rebound number lower than the specimens with silica fume but porosity and permeability higher than specimens with silica fume. The inclusion of mineral admixtures reduced the workability of concrete mixes. Nevertheless, it can be concluded that the mineral admixtures generally improved the compressive strength, ultrasonic pulse velocity, surface hardness and durability of high strength concrete.